Ectendomeliola - a new genus of Meliolaceae - and D.K. AGARWAL, V.B. HOSAGOUDAR* (Indian Phytopathology, 2006)
A new genus of the family Meliolaceae, Ectendomeliola, has been described on the plant Walsura trifolia from Sankili forest in Kerala, India. The type species being E. walsurae.